Postmortem Analysis of 4 Mutation Hotspots of KCNQ1, KCNH2, and SCN5A Genes in Sudden Unexplained Death in Southwest of China. (September 2018) - Jia, Peng-Lin; Wang, Yue-Bing; Fu, Hua; Huang, Wen-Li; Zhong, Shu-Rong; Ma, Lin; Li, Yu-Hua; Dong, Yi; Sun, Zhong-Chun; Yang, Lin; Qu, Peng-Fei; Zhao, Su; et al.
Abstract : Abstract: Long QT syndrome (LQTS) is known to be involved in some sudden unexplained death (SUD) cases. To make clear whether the pathogenic genes of LQTS are involved in SUD in Yunnan province, southwest of China, we examined 4 mutation hotspot segments of KCNQ1, KCNH2, and SCN5A genes in 83 SUD cases using polymerase chain reaction and direct DNA sequencing. Genomic DNA was extracted from paraffin-embedded tissues in 83 cases of sudden cardiac death. One novel homozygous missense variant was identified in exon 3 of KCNQ1, c. 575G>T (p.R192L) in one case. One novel heterozygous missense variant was identified in exon 7 of KCNH2, c.1789T>A (p.Y597N) in 1 case. One novel heterozygous missense variant was identified in exon 7 of KCNH2, c.1800C>A (p.S600R) in 9 cases. In addition, 18 individuals were found to have heterozygous missense variant in exon 7 of KCNH2, c.1801G>A (p.G601S). Our study suggests that some SUDs in Yunnan province may be related with the pathogenic genes of LQTS.